THE ANALYSIS OF VOCABULARY AND LANGUAGE STYLE IN A THOUSAND YEARS SONG BY CHRISTINA PERRI TRANSLITERATED FROM ENGLISH INTO INDONESIAN - Astri Indriana Octavita (Universitas Nasional, 2017)
ABSTRACT The purposes of this research are: to describe the analysis of vocabulary and the types of language style in A Thousand Years lyric by Christina Perri. The method used in this research is descriptive qualitative in analyzing the data by classyfing them into vocabulary and language style. After analyzing A Thousand Years lyric , the writer can conclude that the vocabulary and the types of language style are classified in eight types. First, simple style, such as Heart beats fast. The second, precious and powerful style which is the name implies such as But watching you stand alone. The third, middle style is a style that is directed to attempt to inflict happy and peaceful atmosphere such as Darling don't be afraid. The fourth, climax is a kind of a style that contains sequences mind that every time the increasing importance of the ideas previously such as Time stands still. Beauty in all she is. The fifth, anticlimax such as I will not let anything take away. The sixth, parallelism is a kind of a style that is trying to achieve alignment in the use of words or phrases which occupied the same function and grammatical form such as every breath. Every hour has come to this. The seventh, antithesis such as I have died everyday waiting for you. And the eight, repetition is the parts of words that are considered important to give the pressure in an appropriate context such as I have loved you for a thousand years. Keywords: Vocabulary, The Language Style, Translation Procedure ABSTRAK Tujuan dari penelitian ini adalah: untuk menggambarkan analisis kosakata dan jenis gaya bahasa dalam lirik lagu Thousand Years oleh Christina Perri. Metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif untuk menganalisis data dengan mengklasifikasikanya ke dalam kosa kata dan gaya bahasa. Setelah menganalisis lirik A Thousand Years, penulis dapat menyimpulkan bahwa kosakata dan jenis gaya bahasa diklasifikasikan ke dalam delapan jenis. Pertama, gaya sederhana, seperti jantungku berdebar kencang. Gaya kedua, berharga dan kuat yang namanya seperti namun melihatmu sendirian. Ketiga, gaya tengah adalah gaya yang diarahkan untuk mencoba menimbulkan suasana gembira dan damai seperti kasih jangan takut. Keempat, klimaks adalah semacam gaya yang berisi urutan keberatan bahwa setiap kali semakin penting ide-ide sebelumnya seperti waktu berhenti berputar. Segala tentangnya begitu indah. Kelima, antiklimaks seperti Takkan kubiarkan segalanya berlalu begitu saja. Keenam, paralelisme adalah semacam gaya yang berusaha untuk mencapai keselarasan dalam penggunaan kata atau frasa yang menduduki fungsi yang sama dan bentuk gramatikal seperti Tiap tarikan nafas, Tiap jam telah sampai di sini . Ketujuh, antitesis seperti Tiap hari aku telah mati karena menantimu. Dan delapan, pengulangan adalah bagian dari kata-kata yang dianggap penting untuk memberikan tekanan dalam konteks yang tepat seperti Aku tlah mencintaimu ribuan tahun. Kata Kunci: Kosakata, Gaya Bahasa, Prosedur Penerjemahan